Solid waste wave-absorbing concrete aggregate, preparation method and concrete

By using crushed coal gangue, lithium slag and steel slag of different particle sizes, combined with hydrophobic treatment and carbonization treatment, solid waste absorbing concrete aggregate with high strength and good wave absorption performance is prepared, which solves the problem of insufficient stability and wave absorption performance caused by the steel slag treatment process in the prior art.

CN119661103AActive Publication Date: 2025-03-21JIAHUA SPECIAL CEMENT
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411869760.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

In the prior art, when steel slag is used as coarse aggregate, the thermal slurry treatment process leads to poor stability of concrete and insufficient wave absorption and mechanical properties.

Method used

A solid waste absorbing concrete aggregate, including coal gangue, lithium slag and steel slag of different particle sizes, is used to prepare high-strength and good absorbing properties through crushing, grinding, hydrophobic treatment and carbonization treatment.

Benefits of technology

It improves the stability, strength and wave absorption performance of concrete, solves the stability problems caused by the steel slag treatment process, and achieves better mechanical properties and wave absorption effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to solid waste wave-absorbing concrete aggregate, a preparation method and concrete.The solid waste wave-absorbing concrete aggregate is prepared from, by weight, 18%-22% of coal gangue, 4%-6% of lithium slag, 8%-12% of steel slag with the particle size ranging from 0 mm to 5 mm, 17%-23% of steel slag which is subjected to hydrophobic treatment and has the particle size ranging from 5 mm to 10 mm and 40%-50% of steel slag which is subjected to carbonization treatment and has the particle size ranging from 10 mm to 20 mm. According to the aggregate, the preparation method and the concrete, the problem of poor stability can be effectively solved, and the concrete is higher in strength and better in wave absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a solid waste wave-absorbing concrete aggregate, a preparation method and concrete. Background Art

[0002] Absorbent concrete (also known as cement-based composite absorbing material) is a functional building material that absorbs electromagnetic waves by adding absorbing agents to ordinary cement concrete or by performing special structural design. It has the advantages of energy saving, environmental protection, low price, wide application, strong applicability, etc., while avoiding the disadvantages of easy shedding and damage of coating materials. However, due to the complex composition of cement, when selecting different absorbers, it is necessary to consider the compatibility of the absorber and the cement matrix, as well as the impact of the physical and chemical reactions between them on the absorbing performance, working performance, mechanical properties, etc. of cement-based materials.

[0003] Magnetic absorbers are mainly iron oxide series (Fe3O4, Fe2O3, etc.) and ferrite series (Mn-Zn ferrite, Ni-Zn ferrite, etc.). Magnetic absorbers have high magnetic permeability and generally have good absorbing performance at low frequencies. Conductive absorbers (carbon powder, fiber, etc.) have good conductivity. After being added to concrete, they can form conductive chains or conductive networks and absorb electromagnetic waves through electric field interaction. Conductive absorbers used in concrete are generally carbon-based materials with small specific gravity, but excessive addition will cause a large amount of reflection of the incident wave and reduce the absorbing performance, and will also affect the working performance of concrete. Dielectric absorbers usually have a large dielectric constant and mainly rely on dielectric polarization and interface polarization to absorb electromagnetic waves, such as manganese dioxide, barium titanate ceramics, etc. Due to their weak loss capacity, dielectric loss agents do not significantly improve the absorbing performance of cement concrete. At present, there is little research on dielectric absorbers filled with cement-based composite absorbing materials.

[0004] In the prior art, a Chinese invention patent document with publication number CN114105567A and publication date March 1, 2022 is proposed. The technical solution disclosed in the patent document is as follows: concrete that absorbs electromagnetic waves is prepared from industrial solid waste. This type of concrete consists of 15-25% by weight of powder, 25-35% of fine aggregate, 35-45% of coarse aggregate, 6-10% of liquid and 0.1-0.3% of fiber. Slag and fly ash are added to the concrete, and steel slag is used as coarse aggregate; polypropylene fiber is added to enhance the crack resistance of the concrete.

[0005] The above technical solution may cause the following problems during actual use: Steel slag is used as coarse aggregate and is manufactured using a hot stuffing process. The principle is to use the residual heat of the steel slag and the physical and chemical reaction produced by water to make alkaline oxides such as CaO and MgO react to produce hydroxides. Its own alkalinity has not changed substantially, resulting in poor stability of concrete. Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a solid waste absorbing concrete aggregate, a preparation method and concrete, which can effectively solve the problem of poor stability, and the concrete has higher strength and better absorbing performance.

[0007] The present invention is achieved by adopting the following technical solutions: A solid waste wave-absorbing concrete aggregate comprises, by weight percentage, 18% to 22% of coal gangue, 4% to 6% of lithium slag, 8% to 12% of steel slag with a particle size of 0 mm to 5 mm, 17% to 23% of steel slag with a particle size of 5 mm to 10 mm that has been subjected to hydrophobic treatment, and 40% to 50% of steel slag with a particle size of 10 mm to 20 mm that has been subjected to carbonization treatment.

[0008] The particle size of the coal gangue is 0 mm to 5 mm.

[0009] The particle size of the lithium slag is 45 μm and the sieve residue is 30% to 50%.

[0010] The hydrophobic treatment specifically refers to: soaking steel slag with a particle size of 5mm-10mm in a hydrophobic agent, and drying after fully absorbing it.

[0011] The carbonization treatment specifically refers to: placing steel slag with a particle size of 10mm~20mm in an autoclave, autoclaving it with water vapor at a temperature of 175℃~185℃ for 3h~5h, then releasing the steam and introducing 0.9MPa~1.1MPa cement kiln tail gas, and curing for 3h~5h.

[0012] A method for preparing solid waste wave-absorbing concrete aggregate comprises the following steps: Step S1. crushing the gangue and steel slag respectively, and grinding the lithium slag; Step S2. The crushed slag is screened, the slag with a particle size of 5 mm to 10 mm is hydrophobic, and the slag with a particle size of 10 mm to 20 mm is carbonized; Step S3: Mix the coal gangue, steel slag and lithium slag evenly.

[0013] A solid waste wave-absorbing concrete comprises the solid waste wave-absorbing concrete aggregate.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The present invention breaks the conventional thinking and uses the solid wastes, namely coal gangue, lithium slag and steel slag, which are clearly not allowed to be used in the general Portland cement standard GB175-2023, as concrete aggregates. Through the mutual coordination of various substances, the configuration of high-strength wave-absorbing concrete can be achieved.

[0015] Specifically, the coal gangue is crushed into fine aggregate and can be evenly distributed in the concrete, making the concrete absorbent and conductive, further enhancing the wave absorbing effect; the steel slag is porous and has wave absorbing properties itself, and at the same time, the iron in the steel slag is conductive, which can enhance the wave absorbing effect; the lithium slag can enter the interior of the coal gangue and steel slag, and can also improve the conductive properties.

[0016] Steel slag can improve the activity of coal gangue, mainly by adjusting the pH value and ion concentration of coal gangue, increasing the active functional groups such as hydroxyl and carboxyl on its surface, thereby improving its activity. In addition, trace elements in steel slag can act as catalysts or active centers to further stimulate the reaction activity and stability of coal gangue. At the same time, coal gangue and steel slag can complement each other in hardness and provide suitable aggregate strength for concrete.

[0017] At the same time, lithium slag has good volcanic ash activity. After being ground, it can fill part of the aggregate pores, improve the particle distribution, improve the working performance of concrete, and be more conducive to the development of strength. Furthermore, lithium slag particles provide nucleation points for cement hydration products, which is conducive to the adhesion of hydration products and better exerts the nucleation effect. At the same time, the calcium hydroxide generated by the hydration of steel slag reacts with the active aluminum and silicon in the coal gangue and lithium slag, and the early strength of concrete is improved under the joint action.

[0018] 2. The aggregate of the present invention can achieve good particle grading and the most compact packing by controlling the proportion of each material, thereby reducing the amount of cementitious material in concrete and improving the comprehensive performance of concrete.

[0019] 3. The present invention treats steel slag of different particle sizes separately. The steel slag with a particle size of 5mm-10mm is subjected to hydrophobic treatment, so that the steel slag can retain more of its internal porous structure, which is more conducive to the improvement of wave absorption performance. The steel slag with a particle size of 10mm-20mm is subjected to carbonization treatment to react the alkaline oxides into carbonates. While consuming calcium oxide and magnesium oxide in the steel slag, the alkalinity can be reduced and the stability can be improved, which can solve the problem of aggregate stability. At the same time, CO2 is adsorbed to achieve the effect of carbon fixation.

[0020] The coordination of steel slag of different particle sizes can play a greater role and is more conducive to improving the mechanical properties and wave absorption performance of concrete.

[0021] 4. The hydrophobic treatment method is simple, and the steel slag treated by the hydrophobic treatment has some hydrophobic agent remaining on the surface or in the internal voids. The hydrophobic agent remaining on the surface can effectively reduce the water demand of the steel slag, especially the fine steel slag, and improve the strength of the concrete; the hydrophobic agent remaining in the internal voids can ensure the integrity of the voids and improve the wave absorption performance of the concrete.

[0022] 5. In the present invention, after forming Tobermorite by utilizing the calcium-silicon ratio of steel slag in the carbonization treatment, the carbonized Tobermorite can make the carbonization product more evenly distributed in the steel slag, and at the same time improve the carbonization carbon fixation rate and ensure stability.

[0023] At the same time, the carbonized steel slag also produces some calcium silicate hydrate and calcium carbonate during the autoclaving process. As homogeneous materials, the formed calcium silicate hydrate can serve as a crystal nucleus to activate the uncarbonized part, which can effectively promote the hydration of the hydrophobic treated steel slag, improve the performance of aggregate, and achieve the improvement of the comprehensive performance of concrete.

[0024] 6. When the present invention performs carbonization treatment on steel slag, the flue gas from the cement kiln is introduced, which can make full use of existing resources. DETAILED DESCRIPTION

[0025] Example 1 This embodiment includes a solid waste wave-absorbing concrete aggregate, which includes, by weight percentage, 18% coal gangue, 4% lithium slag, 8% steel slag with a particle size of 0 mm to 5 mm, 20% steel slag with a particle size of 5 mm to 10 mm that has been treated with hydrophobicity, and 50% steel slag with a particle size of 10 mm to 20 mm that has been treated with carbonization. The particle size of the coal gangue is 0 mm to 5 mm. The particle size of the lithium slag is 45 μm and the sieve residue is 30% to 50%.

[0026] The hydrophobic treatment specifically refers to: soaking steel slag with a particle size of 5mm~10mm in a hydrophobic agent, drying after full absorption. Wherein, the hydrophobic agent can be silicone resin or fluorocarbon polymer, etc. The carbonization treatment specifically refers to: placing steel slag with a particle size of 10mm~20mm in an autoclave, steam-compressing it with water vapor at a temperature of 175℃~185℃ for 3h~5h, releasing steam and passing 0.9MPa~1.1MPa of cement kiln tail gas, and curing for 3h~5h. Wherein, the kiln tail gas is the exhaust gas from the calcination of clinker in the cement plant, which is about 150℃ and contains about 25% CO2.

[0027] The method for preparing the solid waste absorbing concrete aggregate comprises the following steps: Step S1. Crush the coal gangue and steel slag respectively, and grind the lithium slag into fine powder.

[0028] Step S2: Screening the crushed steel slag, performing hydrophobic treatment on the steel slag with a particle size of 5 mm to 10 mm, and performing carbonization treatment on the steel slag with a particle size of 10 mm to 20 mm.

[0029] Step S3: Mix the coal gangue, steel slag and lithium slag evenly.

[0030] Example 2 This embodiment includes a solid waste wave-absorbing concrete aggregate, which includes, by weight percentage, 22% coal gangue, 6% lithium slag, 12% steel slag with a particle size of 0 mm to 5 mm, 20% steel slag with a particle size of 5 mm to 10 mm that has been treated with hydrophobicity, and 40% steel slag with a particle size of 10 mm to 20 mm that has been treated with carbonization. The particle size of the coal gangue is 0 mm to 5 mm. The particle size of the lithium slag is 45 μm and the screen residue is 30% to 50%.

[0031] Among them, the hydrophobic treatment method, carbonization treatment method and preparation method of solid waste absorbing concrete aggregate are consistent with the methods in Example 1.

[0032] Example 3 This embodiment includes a solid waste wave-absorbing concrete aggregate, which includes, by weight percentage, 20% coal gangue, 5% lithium slag, 10% steel slag with a particle size of 0 mm to 5 mm, 17% steel slag with a particle size of 5 mm to 10 mm that has been treated with hydrophobicity, and 48% steel slag with a particle size of 10 mm to 20 mm that has been treated with carbonization. The particle size of the coal gangue is 0 mm to 5 mm. The particle size of the lithium slag is 45 μm and the screen residue is 30% to 50%.

[0033] Among them, the hydrophobic treatment method, carbonization treatment method and preparation method of solid waste absorbing concrete aggregate are consistent with the methods in Example 1.

[0034] Example 4 This embodiment includes a solid waste wave-absorbing concrete aggregate, which includes, by weight percentage, 19% coal gangue, 6% lithium slag, 11% steel slag with a particle size of 0 mm to 5 mm, 23% steel slag with a particle size of 5 mm to 10 mm that has been treated with hydrophobicity, and 41% steel slag with a particle size of 10 mm to 20 mm that has been treated with carbonization. The particle size of the coal gangue is 0 mm to 5 mm. The particle size of the lithium slag is 45 μm and the screen residue is 30% to 50%.

[0035] Among them, the hydrophobic treatment method, carbonization treatment method and preparation method of solid waste absorbing concrete aggregate are consistent with the methods in Example 1.

[0036] The solid waste wave-absorbing concrete aggregates in the above-mentioned Examples 1 to 4 are used to make concrete. The concrete mix ratio is shown in Table 1 below: Table 1 Concrete mix ratio kg / m 3 Calcium carbonate was used as common aggregate and concrete was prepared using the mix ratio in Table 1 to form a control group. The concrete prepared in Examples 1 to 4 was compared with the concrete prepared in the control group to test the carbon fixation rate, strength, wave absorption performance and other indicators. The test results are shown in Table 2 below: Table 2 Concrete performance test The carbon fixation rate is calculated by the increase in the mass of steel slag. The compressive strength is measured with reference to GB / T50107-2010 "Standard for Testing and Evaluation of Concrete Strength". The reflectivity is measured with reference to GJB 2038-94 Test Method for Reflectivity of Radar Absorbing Materials.

[0037] It can be seen from the above test data that the concrete prepared by the concrete aggregate of the present application has more stable performance, higher strength and better wave absorption performance.

[0038] In summary, after reading the present invention document, ordinary technicians in this field can make various other corresponding transformation schemes based on the technical scheme and technical concept of the present invention without creative mental labor, which all fall within the scope of protection of the present invention.

Claims

1. A solid waste absorbing concrete aggregate, characterized by: In terms of weight percentage, it includes 18% to 22% of coal gangue, 4% to 6% of lithium slag, 8% to 12% of steel slag with a particle size of 0mm to 5mm, 17% to 23% of hydrophobic treated steel slag with a particle size of 5mm to 10mm, and 40% to 50% of carbonized steel slag with a particle size of 10mm to 20mm.

2. The solid waste absorbing concrete aggregate according to claim 1, characterized in that: The particle size of the coal gangue is 0 mm to 5 mm.

3. The solid waste absorbing concrete aggregate according to claim 1, characterized in that: The particle size of the lithium slag is 45 μm and the sieve residue is 30% to 50%.

4. The solid waste absorbing concrete aggregate according to claim 1, characterized in that: The hydrophobic treatment specifically refers to: soaking steel slag with a particle size of 5mm-10mm in a hydrophobic agent, and drying after fully absorbing it.

5. The solid waste absorbing concrete aggregate according to claim 1, characterized in that: The carbonization treatment specifically refers to: placing steel slag with a particle size of 10mm~20mm in an autoclave, autoclaving it with water vapor at a temperature of 175℃~185℃ for 3h~5h, then releasing the steam and introducing 0.9MPa~1.1MPa cement kiln tail gas, and curing for 3h~5h.

6. The method for preparing a solid waste wave-absorbing concrete aggregate according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1. crushing the gangue and steel slag respectively, and grinding the lithium slag; Step S2. The crushed slag is screened, the slag with a particle size of 5 mm to 10 mm is hydrophobic, and the slag with a particle size of 10 mm to 20 mm is carbonized; Step S3: Mix the coal gangue, steel slag and lithium slag evenly.

7. A solid waste absorbing concrete, characterized in that: It includes the solid waste wave-absorbing concrete aggregate as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Environment-friendly concrete capable of absorbing electromagnetic waves and preparation method thereof

    CN114105567A

  • Pumice concrete with the function of electromagnetic wave absorption, and preparation method thereof

    CN102627436A

  • Building wave-absorbing coating based on magnesium oxide excited steel slag and preparation method thereof

    CN112812612A

  • Steel slag granulation method based on microwave strengthening and product prepared by same

    CN118389756A

  • Method for manufacturing electromagnetic shielding remital using solid carbon capsules and steelmaking slag aggregate

    KR102553066B1